EXCESS DIETARY SUGAR ALTERS COLONOCYTE METABOLISM AND IMPAIRS THE EARLY PROLIFERATIVE RESPONSE TO DAMAGE. (26th January 2023) - Burr, Ansen; Ji, Junyi; Ozler, Kadir; Mentrup, Heather; Eskiocak, Onur; Cumberland, Rachel; Menk, Ashley; Zhang, Xiaoyi; Overacre-Delgoffe, Abigail; Rittenhouse, Natalie; Marshall, Chris; Cooper, Vaughn; et al.
Abstract: The colonic epithelium requires continuous renewal by crypt resident intestinal stem cells (ISCs) and transit amplifying (TA) cells to maintain barrier integrity, especially after inflammatory damage. An important regulator of ISC and TA cell function is dietary metabolites which can affect their proliferative capacity. Over the last 150 years, the diet of high-income countries contains increasing amounts of simple sugars, such as sucrose, but whether excess sugar affects the function of ISCs and TA cells directly is unknown. We used a combination of 3-dimensional colonoids and a mouse model of colon damage/repair (DSS colitis) to demonstrate the direct effect of sugar on the transcriptional, metabolic, and regenerative functions of crypt ISCs and TA cells. We demonstrate that high sugar conditions directly limit murine and human colonoid development, which is associated with a reduction in the expression of proliferative and key stem cell gene signatures. Further, high-glucose conditions led to the accumulation of glycolytic metabolite pyruvate in colonoids, with a concomitant decrease in ATP, suggesting impaired glycolytic fuel metabolism. Treatment of colonoids with DCA, which forces pyruvate into the TCA cycle, restored their growth, ATP levels, and the expression of proliferation and stem cell gene signatures. Similarly, DSS treatment of mice fed a high sugar diet led to massive irreparable damage that was independent of the colonic microbiota and its metabolites. Metabolic analyses of crypt cells from high-sucrose-fed mice revealed increased glycolytic potential without a commensurate increase in aerobic respiration. Rather, epithelium from high-sucrose-fed mice has increased mitochondrial content, without increased levels of ATP, further demonstrating impaired oxidative phosphorylation and fuel metabolism. Finally, we demonstrated impaired proliferative potential of ISCs and reduced number of TA direct daughter cells in high-sucrose-fed mice with DSS damage. Taken together, our results indicate that short-term, excess dietary sucrose can directly modulate intestinal crypt cell metabolism and inhibit ISC/TA cell regenerative proliferation. This knowledge may inform diets that better support the treatment of acute intestinal injury, as is seen in patients with an acute flare of Ulcerative Colitis.